Journey to a better "Mchare" - Improving Tanzania cooking banana - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Journey to a better “Mchare” “Mchare” is an important cooking banana in Tanzania and parts of Eastern Africa. Its production, and hence the food and income of millions of smallholder farmers, are currently threatened by several pests and diseases attacking the crop including black sigatoka, fusarium wilt, weevils, and nematodes. IITA has established the first ever breeding program for the crop in Arusha, Tanzania, and together with their national and international partners, IITA researchers are working diligently to develop high-yielding disease resistant hybrid “Mchare”. This is an arduous task due to the sterile and sexless nature of banana. In this video, the team shows the difficult process in breeding for better “Mchare”. In addition to this program, the IITA banana breeding team and its partners in Uganda and Nigeria are breeding “Matooke” and plantain, respectively. These are the most important cooking banana and plantain for food security in Africa.